Fabrication and Characterization of Fabric-reinforced Pressure Retarded Osmosis Membranes for Osmotic Power Harvesting - She, Qianhong (2016)
In recent years, pressure retarded osmosis (PRO) has attracted increasing interest in the harvesting of the renewable osmotic power. However, its performance can be significantly influenced by the membrane deformation in the operation when the PRO membrane is lack of sufficient mechanical strength. In this study, we fabricated three different fabric-reinforced thin-film composite (TFC) flat-sheet PRO membranes for osmotic power harvesting. These membranes were prepared through integrating three different types of fabric reinforcement (i.e., tricot fabric, woven fabric and nonwoven fabric) in the membrane substrate layer. It was found that the fabric reinforcement plays an important role in the membrane structural property and mechanical property, both of which can significantly influence the PRO performance. The nonwoven-fabric-reinforced membrane had the greatest structural parameter and thus exhibited the lowest performance. Although the tricot-fabric-reinforced membrane and the woven-fabric-reinforced membrane had similar performance in the forward osmosis (FO) condition (ΔP=0), the former showed superior performance in the PRO condition (ΔP>0). This is mainly because the tricot-fabric-reinforced membrane had better mechanical resistance to the multi-directional tensile stretching, which rendered it less prone to changes in structural and separation properties in the PRO operation. This further suggests that the tricot fabric has high potential for future PRO membrane fabrication. The current study also elaborates the coupled effects of compression and stretching on PRO membrane deformation and performance. The results obtained in this study may provide important insights into reinforced PRO membrane design.